Regional citrate anticoagulation for continuous renal replacement therapy in newborns - Huang, Haixia; Deng, Xing; Bai, Ke; Liu, Chengjun; Xu, Feng; Dang, Hongxing (Frontiers in Pediatrics, 2023)
Objective: Continuous renal replacement therapy (CRRT) is increasingly used in neonates, but there are few ones, anticoagulated with citrate anticoagulation (RCA), reported in neonates. The purpose of this study was to evaluate the safety and efficacy of RCA-CRRT in neonates, explore the risk factors of citrate accumulation (CA), and optimize the RCA-CRRT regimen. Methods: This retrospective observational study reviewed the clinical records of neonates who underwent RCA-CRRT at our pediatric intensive care unit between 2015 and 2021. Results: A total of 23 neonates underwent 57 sessions of RCA-CRRT, with a mean age of 10.1±6.9 days and a mean weight of 3.0±0.7 kilogram (range, 0.95 to 4 kilogram). The mean filter lifespan was 31.54±19.58 hours (range, 3.3 to 72.5 hours). There were 128(61.8%) sessions of ionic calcium in vitro(iCaE)below0.4mmol/L, and the average iCaE was 0.37±0.08 mmol/L during RCA-CRRT. Compared with before RCA-CRRT, Ph and HCO3- increased significantly after RCA-CRRT, but the incidence of total/ionized calcium ratio(T/iCa) above 2.5, in vivo calcium below 0.9mmol/L, hypernatremia and hyponatremia had no significant difference. After RCA-CRRT, there were 30 sessions of T/iCa below 2.5(NCA group) and 5 sessions of T/iCa above 2.5(CA group), suggesting that the incidence of T/iCa above 2.5 was 14.3%. Compared with the NCA group, the CA group had significantly greater body weight and significantly smaller QB/BW; however, there was no significant difference between the two groups in terms of age, corrected gestational age, PRISM-Ⅲ Score, or biochemical tests such as PT, APTT, TB, DB, AST, ALT, GGT, Lac, or terminal parameters such as QCi/QB, QCa/QB (QD+ QF)/BW. Conclusions: RCA-CRRT is safe and effective for neonates. With proper adjustment of RCA-CRRT parameters, the incidence of CA was not higher than that of children or adults, and there was no significant correlation between CA and age or corrected gestational age. Keywords: Citrate accumulation, continuous renal replacement therapy, newborns, regional citrate anticoagulation